STRESS INTENSITY FACTORS FOR CIRCUMFERENTIAL PERIODIC CRACKED PIPES UNDER BENDING - LIU WanJun; XIE YuJun (Jixie qiangdu)
Stress intensity factor is an important parameter that characterizes the stress field near the tip in fracture analysis. The simple and effective methods to estimate intensity factor become significant. Based on the J2 conservation integral, a simple exact method is proposed to determine the stress intensity factor for periodic cracked pipe under the bending effect. The principle of this method is clear and the calculation process is simple.